(untitled) (Jurnal Adabiya, 2025)
This study evaluates the digital collection management at the STiPRAM e-library using the Six-Ware framework, which includes software, hardware, netware, dataware, brainware, and environmentware. The e-library utilizes software like e-print, Vufind, and Slims for managing repositories, e-journals, and e-books, supported by a large-capacity server for efficient storage and fast access. Networking is facilitated via intranet and internet, with access restrictions for certain collections. Digital collections are primarily in text (PDF format), with multimedia available only in physical formats. The library is managed by personnel skilled in information technology, and users receive training to independently access digital resources. Initially, the limited number of staff posed challenges in managing both conventional and digital libraries, but this issue was addressed by increasing staff and improving coordination. Overall, the STiPRAM e-library effectively integrates technology for managing digital collections, enhancing access for users, though further improvements in multimedia management and network capacity are needed. ABSTRAK Penelitian ini mengevaluasi pengelolaan koleksi digital di e-library STiPRAM menggunakan kerangka Six-Ware, yang meliputi software, hardware, netware, dataware, brainware, dan environmentware. E-library ini menggunakan perangkat lunak seperti ehard-print, Vufind, dan Slims untuk mengelola repository, e-jurnal, dan e-book, didukung oleh server berkapasitas besar untuk penyimpanan yang efisien dan akses yang cepat. Jaringan menggunakan intranet dan internet, dengan pembatasan akses pada beberapa koleksi. Koleksi digital umumnya dalam bentuk teks (format PDF), sementara multimedia hanya tersedia dalam format fisik. Perpustakaan ini dikelola oleh tenaga terampil di bidang teknologi informasi, dan pengguna diberikan pelatihan untuk mengakses sumber daya digital secara mandiri. Pada awalnya, jumlah staf yang terbatas menjadi kendala dalam mengelola perpustakaan konvensional dan digital secara bersamaan, namun masalah ini dapat diatasi dengan penambahan staf dan koordinasi yang lebih baik. Secara keseluruhan, e-library STiPRAM berhasil mengintegrasikan teknologi untuk pengelolaan koleksi digital, meningkatkan akses bagi pengguna, meskipun masih diperlukan perbaikan dalam pengelolaan multimedia dan kapasitas jaringan